Biological control agents for the soil pathogen management and whitefly on bell pepper crop. “Capsicum annum”. - Portalanza Peralta, Diego Enrique; Vivas Vivas, Leticia (Revista Universidad de Guayaquil, 2011)
The bell pepper crop (Capsicum annum L.), is affected by plant pathogens that cause the wilt complex, plague insects such as whitefly, Bemisia tabaci, vector of some viruses e.g. Geminiviruses. The specific objectives were: 1) to determine doses and frequencies of application of T. asperellum over bell pepper wilt complex, and 2) to determine doses and frequencies of application of B. bassiana for Bemisia tabaci management. In both studies a completely randomly plot design with three replicates was used and the Duncan multiple range test p = 0.05 was used for the means comparison. The bell pepper wilt was caused by: Fusarium sp., Rhizoctonia sp., Sclerotium rolfsii y Ralstonia solanacearum. The lower severity was observed with T. Asperellum 45 x 106 spores/L applied 7 days after the transplant. In the study of doses and frequencies of application of B. bassiana for the B. tabaci management, 1x106 applied ten days after the transplant dose showed the lowest presence of white fly per plant. The best yields were B. bassiana applied 10 days after the transplant at a dose of one and ten million spores with an average of 14 and 13TM.